Urgensi Jaminan Sosial dalam Memberikan Kepastian Hukum Bagi Pekerja Rumah Tangga di Kabupaten Bekasi - Cut Adelia Maharani; Melinda Riyanti Tanjung; Nabila Syka Anggita; Syalsya Syabilla Suherman; Rismanro Simatupang (DPPM Universitas Pelita Bangsa, 2026)
This study examines the relevance of social security in strengthening legal certainty for Domestic Workers (PRT) and evaluates the role of the Bekasi Regency Government in implementing such protection. Using a qualitative approach with a case study in Bekasi Regency, data were collected through a review of regulatory documents, semi-structured interviews with domestic workers, employers, and related institutions, as well as field observations on work practices and access to social security. The findings indicate that social security—particularly BPJS Employment programs such as Work Accident Insurance (JKK) and Death Insurance (JKM)—functions not only as a protection mechanism but also as a formal instrument recognizing the status of domestic workers as legitimate workers. Registered domestic workers reported receiving direct benefits. These findings reaffirm that participation in social security strengthens legal recognition, provides certainty in employment relations, and places employers within a clearer legal responsibility framework.